(untitled) - Stuller, John A. (Southbank, Vic., 2008)
This book provides a concise and clear introduction to signals and systems theory, with emphasis on fundamental analytical and computational techniques. Introduction to Signals and Systems develops continuous-time and discrete-time concepts/methods in separate chapters - highlighting the similarities and differences - and features introductory treatments of the applications of these basic methods in such areas as filtering, communication, sampling, discrete-time processing of continuous-time signals, and feedback. This text is written for introductory courses in continuous-time and/or discrete-time signals and systems for Electrical Engineering students. It is also accessible to a broad range of engineering and science students, as well as valuable to practicing engineers seeking an insightful review.
Keywords: Signal theory (Telecommunication),System analysis,Signal processing,Lý thuyết tín hiệu (viễn thông),Sự phân tích hệ thống,Sự phát tín hiệu